Stability and Assembly of Pilus Subunits of Streptococcus pneumoniae - El Mortaji, Lamya (American Society for Biochemistry and Molecular Biology, 2010)
Pili are surface-exposed virulence factors involved in bacterial adhesion to host cells. The Streptococcus pneumoniae pilus is composed of three structural proteins, RrgA, RrgB, and RrgC and three transpeptidase enzymes, sortases SrtC-1, SrtC-2, and SrtC-3. To gain insights into the mechanism of pilus formation we have exploited biochemical approaches using recombinant proteins expressed in Escherichia coli. Using site-directed mutagenesis, mass spectrometry, limited proteolysis, and thermal stability measurements, we have identified isopeptide bonds in RrgB and RrgC and demonstrate their role in protein stabilization. Co-expression in E. coli of RrgB together with RrgC and SrtC-1 leads to the formation of a covalent RrgB-RrgC complex. Inactivation of SrtC-1 by mutation of the active site cysteine impairs RrgB-RrgC complex formation, indicating that the association between RrgB and RrgC is specifically catalyzed by SrtC-1. Mass spectrometry analyses performed on purified samples of the RrgB-RrgC complex show that the complex has 1:1 stoichiometry. The deletion of the IPQTG RrgB sorting signal, but not the corresponding sequence in RrgC, abolishes complex formation, indicating that SrtC-1 recognizes exclusively the sorting motif of RrgB. Finally, we show that the intramolecular bonds that stabilize RrgB may play a role in its efficient recognition by SrtC-1. The development of a methodology to generate covalent pilin complexes in vitro, facilitating the study of sortase specificity and the importance of isopeptide bond formation for pilus biogenesis, provide key information toward the understanding of this complex macromolecular process.